DISHARMONI PELAKSANAAN ANTARA EKSTRADISI DAN DEPORTASI DALAM HAL PENEGAKAN HUKUM DI INDONESIA - bakhtiar, masdar; Kadriah, Awaluddin (Polteknik Imigrasi, 2022)
Abstract The extensibility of law enforcement, in the international arena, enters the modern worldview, which is influenced by the increasingly easy flow of human migration, causing many criminals to move to other countries to avoid punishment in the country where they committed the crime. So law enforcement requires that law enforcement be possible against crimes outside the territorial country where the crime occurred, or the return of the perpetrator to the country where the crime was committed by him. The formulation of the problem under study is how the conflict of norms between the extradition instrument and the deportation instrument in terms of law enforcement in Indonesia. The research method is normative research. The conclusion is that there is a conflict of norms between the extradition instrument and the deportation instrument in terms of law enforcement in Indonesia that in cases that should have been extraditioned but carried out deportation, English translation. so that it is inconsistent with the principle of Lex Superior derogat legi inferiori in terms of substanceThe Extradition Regulation is superior where in article 36 paragraph (2) of the Extradition Law the authority to carry out extradition is in the hands of the president, while in general immigration arrangements in the Immigration-Law including deportations are within the authority of the Minister. English translation. In the level of authority, of course, the authority of the President can be considered superior to the authority of the Minister.English translation. Keywords: Norms, Conflagration, Extradition, Deportation,